PENINGKATAN KETERAMPILAN KEWIRAUSAHAAN SISWA SMK DENGAN MENGGUNAKAN PERSONA CANVAS DAN BUSINESS MODEL CANVAS - Tanaya, Olivia; Candra, Susila; Susanto, Herman; Soesanti, Arum (LPPM Universitas Bina Bangsa, 2025)
Of Indonesia's population, the majority are of productive age, presenting both opportunities and challenges. While this demographic could drive economic progress, limited job vacancies pose a significant issue for young people. Encouraging entrepreneurship is one solution to this problem. A two- day service program was conducted at a private vocational school in Surabaya. The results of pre-test and post-test comparisons revealed improved knowledge, particularly in using Persona Canvas and Business Model Canvas. The Persona Canvas method encourages students to analyze potential buyers' conditions, helping them understand customer needs and problems. Meanwhile, Business Model Canvas, with its nine components, guides students in considering business sustainability. This shift broadened their perspective from focusing solely on technical skills and product sales to recognizing multiple aspects vital to gaining a competitive edge. Participant feedback confirmed that this training effectively nurtures entrepreneurial mindsets, equipping the younger generation with essential skills for future success.